The effectiveness of teachers' corrective feedback on changing the level of assertiveness and connection with the school of students - Talat Sabbagh Hasanzadeh (مطالعات روانشناسی تربیتی)
The purpose of the research was to the effectiveness of teachers' corrective feedback on changing the level of self-expression and connection with the school of students. The research method was semi-experimental with a pre-test/post-test design with a control group. The sample consisted of 40 female elementary school students in Mashhad, who were selected by multi-stage cluster random method and randomly assigned to experimental groups (receiving feedback based on Butler and Wein's model) and controls. In the intervention phase, the experimental group received feedback based on the Butler and Wayne model for 12 weeks, and the control group received traditional feedback. The data collection tool was self-expression and connection with the school questionnaire, which was used in the pre-test and post-test stages for both experimental and control groups. The research data were analyzed by multivariate covariance analysis. The findings indicated that the level of self-expression, and connection with the school of the experimental group had increased significantly compared to the control group. Therefore, it can be said that providing feedback based on the Butler and Wayne model can be effective, and if teachers use this model to provide feedback after formative evaluations, they can increase the level of self-expression and connection with the school of knowledge. Increase students significantly.